Stock Market in Times of Current Crises - Kříž, Matyáš; Taušer, Josef; de Batz de Trenquelléon, Laure Sabine Marie; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
Diploma thesis focuses on the impacts of current crises on the stock market. It utilizes an event study methodology with the market model to analyze impacts of the Covid-19 pandemic and the Russian invasion into Ukraine on benchmark indices of thirty of the largest economies around the world. Additionally, it identified the impacts on ten different industries through sector indices divided according to the GICS methodology. In total the impacts of eight event are analysed in the thesis, four for each of the crises. Overall, for five out of eight events statistically significant impact are identified visible on the cumulative abnormal returns. The thesis also shows the limitations of using the market model for analysing impacts of events of such global significance as the Covid-19 pandemic.
Vedoucí práce: Josef Taušer
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses